Understanding teacher attraction and retention drivers: addressing teacher shortages - Ashiedu, Jennifer; Scott-Ladd, Brenda (Social Science Press, 2012)
The attraction and retention of teachers is a problem faced by schools worldwide and possibly more so in the public sector. One possible solution to this problem is likely to be better targeting of attraction and retention drivers of value to teachers. This paper presents the findings from a qualitative study conducted in Australia. The study used electronic in-depth interviews and an online survey to interrogate the reasons teachers are attracted to the profession and what drives their decision to either stay or leave. Participants in the study were both serving and retired teachers. The majority of respondents cited intrinsic motivators as the reasons for joining the teaching profession and among the serving teachers, those with higher intrinsic motivational drivers exhibited a more positive intention to remain. While both groups viewed extrinsic rewards in the form of pay, the school environment and working conditions as important, intrinsic motivation had most influence on intention to stay in the profession.